Penyesuaian Diri Dan Homesickness Pada Mahasiswa Rantau - Orah, Keysie Debora; Purnawinadi, I Gede (Fakultas Ilmu Keperawatan Universitas Klabat, 2025)
Homesickness is an emotional condition of an individual experiencing distress or discomfort due to separation from their living environment, which if prolonged will negatively impact the academic success and achievement of out-of-town students. Therefore, the ability to adapt becomes very important for out-of-town students in a new environment. The purpose of this study was to determine the relationship between adjustment and homesickness in first-year out-of-town students living in the dormitory of Klabat University. The research method used was quantitative through a cross-sectional approach, with the Spearman correlation test. The sampling technique used the total sampling method with a sample size of 90 respondents. The results of the study stated that 90 (100%) respondents had very high adjustment. For homesickness, the majority of 90 respondents were found to be in the high category, as many as 64 (71.1%). The results of the study showed a significant relationship between adjustment and homesickness in first-year out-of-town students with a low correlation, p-value = 0.000 (<0.05) with a correlation coefficient value of r = -0.411. Recommendations for further research include looking for other factors that can influence homesickness in students living away from home, such as gender factors. Homesickness merupakan suatu kondisi emosional dari individu dimana mengalami distress atau perasaan tidak nyaman karena terpisah dengan lingkungan tempat tinggal yang jika berlangsung lama akan berdampak negatif terhadap keberlangsungan dan pencapaian akademis mahasiswa rantau, oleh karena itu kemampuan menyesuaikan diri menjadi hal yang sangat penting bagi mahasiswa rantau dalam lingkungan yang baru. Tujuan penelitian ini untuk mengetahui hubungan penyesuaian diri dengan homesickness pada mahasiswa rantau tingkat 1 yang tinggal di asrama Universitas Klabat. Metode penelitian yang digunakan yaitu kuantitatif melalui pendekatan cross-sectional, dengan uji spearman correlation. Teknik pengambilan sampel menggunakan motode total sampling dengan jumlah sampel 90 responden. Hasil penelitian menyatakan bahwa 90 (100%) responden mempunyai penyesuaian diri sangat tinggi. Untuk homesickness dari 90 responden didapati mayoritas berada pada kategori tinggi sebanyak 64 (71,1%). Hasil penelitian terdapat hubungan signifikan antara penyesuaian diri dengan homesickness pada mahasiswa rantau tingkat 1 dengan korelasi rendah, p-value=0,000(<0,05) dengan nilai koefisein korelasi r = -0,411. Rekomendasi untuk penelitian selanjutnya dapat mencari faktor lain yang dapat mempengaruhi homesickness pada mahasiswa rantau seperti faktor gender.